The survival of outward investments from China and India: Is there a North-South divide? - Athreye, Suma; Saeed, Abubakr; Saad Baloch, Muhammad (Journal of business research, 2023)
Multinationals from China and India courted the economies of both the North and the South and they had different advantages in doing so. After more than two decades of successful internationalization, can the survival of Chinese and Indian investments reveal the factors that are associated with the success of EMNC investments in the North and the South? This is the main question we explore in this paper. We find that there is a North-South divide in the survival of Chinese and Indian outward investments. Investments in the North are subject to more intense competitive pressure due to the stronger technological and managerial abilities of domestic firms and survival is markedly weaker there. In Southern locations, where Chinese and Indian firms enjoy competitive advantages and industrial leadership in several areas, they also have better rates of survival. Apart from highlighting the role of relative (to host country firms) firm-specific advantages in explaining survival in the North and South, we also find that a larger diaspora in Southern locations is associated with greater survival.